L’invenzione della scoperta. Il sonnambulismo magnetico tra Mesmer e Puységur - Armando, David (Il sogno della farfalla, 2023)
1784 the marquis of Puységur announced the discovery of a state of lucid sleep characterized by extraordinary psychic faculties. This event became crucial in the reconstruction of the origin of modern dynamic psychiatric. According to H. F. Ellenberger, only because of the transition from animal magnetism to magnetic somnambulism, the inner value of Mesmer’s ideas was revealed, paving the way to 19th century hypnotism and to psychoanalysis. Based on a wide unpublished documentation, this article aims to analyze the established narrative and bring into question two specific and crucial aspects: the unexpected and sudden nature of the discovery and the substantial continuity from Mesmer’s materialism, based on the action of the magnetic fluid, to the strictly psychological formulation of artificial somnambulism.